An investigation into the effect of Coronavirus‐2019 (SARS‐CoV‐2) on active transportation as an opportunity to develop a sustainable tourist destination in the postpandemic era with an emphasis on the local community (Case study: Dorood City, Lorestan Province, Iran) - S. S. Hosseini; Y. Gholami; H. Dolvand; Z. V. Ataev (Юг России: экология, развитие)
The aim of this study is structural modeling of the impact of the coronavirus pandemic on active post‐pandemic transport in Dorood City, Iran, emphasising both tourism and development of a long‐term tourist market through the promotion of low‐carbon travel markets.The research tool was a researcher‐made questionnaire randomly distributed among citizens of Dorood City. The impact of various factors, including economic, social, medical, and accessibility, on active transportation during the pandemic and its impact on transportation in the post‐COVID‐19 era has been investigated.The social factor has the highest factor load with a weight of 0.94. In contrast, with the lowest factor load i.e., 0.60, the economic factor proved to have the least impact on the choice of active transportation. It was found that the variable of active transport use in the post‐pandemic era with a factor load of 0.66 is the most influential factor, while the social consequences of the pandemic in the post‐pandemic era with a factor load of 0.49 turned out to be the most significant. The least effective ariable was found to occur in the post‐pandemic era.Active transport links during the pandemic in Dorood City with a regression coefficient of 0.77 had a statistically significant impact on the use of this type of transport in the post‐pandemic period. This data can be incorporated in the transport development plan with an emphasis on active transfer as an effective option for the development of sustainable tourism.